Strategic Realism and Global Engagement: Prime Minister Lee Hsien Loong's International Thinking - Hue, Truong Thi (Hasanuddin University, 2025)
Singapore's unique geopolitical context has long necessitated a foreign policy grounded in pragmatism, strategic foresight, and a deep understanding of global dynamics. Among Singapore's leaders, Prime Minister Lee Hsien Loong stands out for his nuanced international thinking, which balances realism with multilateral engagement, and national interests with global responsibilities. This paper explores the key themes of Lee Hsien Loong's worldview-including globalization, China's rise, the importance of the United States, and regional cooperation, and examines how these have shaped Singapore's foreign policy. Through a qualitative analysis of public speeches, interviews, and secondary literature, the article provides a comprehensive assessment of Lee's international outlook, arguing that it represents a strategic synthesis of small-state survivalism and liberal internationalism.